Critical Success Factors in the Implementation of Electronic Health Records: A Two‐Case Comparison. (30th August 2013) - Standing, Craig; Cripps, Helen
<x xml:space="preserve">Abstract</x> The critical success factors that contribute to the successful implementation of electronic health (e‐health) records are still not clear from the literature. Although many studies have been conducted on the successful adoption of technology, they rarely consider the context of adoption. Given that the health sector in most countries provides a complex environment for the implementation of technology, the context becomes highly significant. The authors use case studies from Slovenia and Australia to identify the factors impacting on successful e‐health implementation. Although Slovenia has progressed much further down the road of e‐health than Australia, the contextual factors were important in both cases. The systemic implications for research and practice are discussed. Copyright © 2013 John Wiley & Sons, Ltd.